Trends in National-Level Governance and Implementation of the Philippines' Responsible Parenthood and Reproductive Health Law from 2014 to 2020 - Siy Van, Vanessa T (Archīum Ateneo, 2021)
In 2012; the Philippines passed the Responsible Parenthood and Family Planning Law; a landmark legislation billed as a multisectoral and rights-based approach to further sustainable human development. This article is part of the first comprehensive evaluation of the implementation of the law by national-level actors. This evaluation is intended to assess the progress of implementers in the conduct of mandates; roles; and responsibilities described in the law and its implementing guidelines. Interviews with key national government officials and data from official documents and literature revealed 3 major trends in governance and implementation from 2014 to 2020. First; despite being a multisectoral policy; performance was siloed within individual units of implementing agencies; with limited interagency coordination. Second; although the law explicitly called for interventions to invest in human capital and address socioeconomic disparities for sustainable human development; performance focused on biomedical and health interventions; particularly in the area of family planning. Third; national-level governance for reproductive health interventions concentrated on programmatic and operational concerns. Overall; this case in the Philippines illustrates that fragmented implementation has contributed to the slow improvement of reproductive health outcomes. This study highlights the challenges of governance and multisectoral coordination to implement multidimensional interventions in a low- and middle-income country; and it provides potential areas for political and administrative reform in reproductive health governance in the Philippines. By creating a common narrative and onboarding multiple sectors; officials can better identify and address structural determinants with holistic policy solutions to improve reproductive health outcomes.